Virtual Reality as a Tool for Immersive Language Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Virtual reality (VR) has emerged as a disruptive tool in education, providing immersive environments that mimic real-world experiences.  In the context of language study, VR allows students to practice listening, speaking, and comprehending in realistic, interactive environments.  This paper investigates how VR improves language acquisition through contextual immersion, enhanced learner engagement, and cultural exposure.  It also covers the existing applications, pedagogical benefits, and obstacles of using VR into language instruction.  The findings indicate that VR has the potential to transform language learning by making it more effective, interesting, and learner-centered.